ANALYSE COMPARATIVE DES RECETTES DE LA DIRECTION GENERALE DES DOUANES ET ACCISES D’ISIRO AVANT ET PENDANT L’APPLICABILITE DE LA TAXE SUR LA VALEUR AJOUTEE A L’IMPORTATION - Oseyatoko, Marcel; LEKABUSIA, Joseph ANDAMA; YAO, Marcel OSEYATOKO (IJRDO - Journal of Business Management, 2018)
The present study relates to the analysis of the receipts of the Directorate-General of the Customs and Accises of Isiro (Dgda-isiro) before and during the applicability of the Value-added tax (VAT) to the importation, of 2008-2015.¶Our concern consists in knowing which two periods, knows the receipts with a positive slope, i.e. a situation which makes it possible at the State to flow its case. ¶After the investigations, one noted what follows:¶ ü Under the ICA the slope of the receipts knew a sinusoidal pace with a successive rate of increase of about 267,51%, 250,16% and 10166,96% of 2008-201;¶ ü As for the period under the VAT, the receipts took an ascending form only of 2012 to 2013, that is to say an increase in 146,72%;¶2014 to 2015, the slope is negative, with a successive fall of about 25,52% and 0,91%.¶